Pharmacological Evaluation Of Orthosiphon Stamineus Extract And Development Of Analgesic Meter For Arthritic Rat Model - Yam, Mun Fei (2012)
Orthosiphon stamineus Benth. is a genus of herb of the family Labiatae or Lamiaceace traditionally used for treatment of many diseases such nephritis, nephrolithiasis, hydronephrosis, vesical calculi, arteriosclerosis, rheumatism, inflammation, gout and diabetes. Despite the availability of modern medications, the use of traditional medicine is growing throughout the world, indicating a need for scientific investigations into the therapeutic effects of medicinal plants and their underlying mechanisms. While no previous investigation has thoroughly reported its pharmacological activities such as anti-ulcer, anti-inflammatory, anti-pyretic, analgesic, hepatoprotective and toxicological effect of such a widely used medicinal herb, this investigation set out to further characterize the traditional claims. The O. Stamineus leaves were dried, pulverized and successively extracted with 50% methanol using maceration method. The extract was dried under reduced pressure and freeze-dried. The yield of lyophylized 50 % methanolic extract of O. Stamineus (SEOS) was found to be 6%. HPLC analysis showed that SEOS contains 0.46%, 1.12%, and 0.94% of 3’-hydroxy-5,6,7,4’- tetramethoxyflavone, sinensetin and eupatorin, respectively. In acute toxicity study, up and down method (limit dose) was adapted. A single dose of 5000 mg/kg of SEOS was given orally to 5 healthy Sprague Dawley (SD) male and female adult rats. The rats were observed for mortality and clinical signs for 3 h and then periodically for 14 days. In the subchronic toxicity study, the extract was administered orally at doses of 1250, 2500 and 5000 mg/kg per day for 28 days to female and male SD rats, respectively. The animals were sacrificed, followed by examination of their organs and blood serum. The results in the acute study showed that SEOS at a dose of 5000 mg/kg caused neither visible signs of toxicity nor mortality. All five rats survived until the end of observation period. While in subchronic toxicity, administration of the SEOS at 1250, 2500, and 5000 mg/kg for 28 days did not produce any mortality and there were no significant differences in the general condition, growth, organ weights, hematological parameters, clinical chemistry values and macroscopic appearance of the organs from the treatment groups as compared to the control group.